Protection and Immune Responses Elicited by rSAG1-PLGA Nanoparticles in C57BL/6 Against Toxoplasma gondii - Mojgan Allahyari; Samira amiri; Alireza Vatanara; Majid Golkar (Pasteur Institute of Iran, 2021)
Introduction: This study aimed to evaluate rSAG1-PLGA efficacy as a particulate vaccine in conferring protection against Toxoplasma gondii infection in C57BL/6 mice. In light of our previous studies, we studied mice genotype role in eliciting immune responses by rSAG1-PLGA nanoparticles in this study. Methods: Poly (DL-lactide-co-glycolide) (PLGA) nanoparticles loaded by rSAG1 as a subunit vaccine were prepared, and C57BL/6 mice were subcutaneously immunized twice at a 3-week interval by rSAG1-PLGA, soluble rSAG1, blank PLGA, and one group kept unvaccinated. The characteristics of PLGA nanoparticles, the amounts of produced IFN-γ, IL-10, specific anti-ToxoplasmaIgGs, and the conferred protection against infection by T. gondii RH tachyzoite were assessed. Results: rSAG1-PLGA nanoparticles shared a z-average of about 450nm with negative Zeta potential. Compared with the negative control group, the mice vaccinated with rSAG1-PLGA nanoparticles produced significantly higher amounts of IFN-γ, specific anti-T. gondii IgG antibodies and higher titer of IgG2a, which resulted in longer survival times. Conclusion: The efficiency of rSAG1-PLGA nanoparticles in inducing humoral and cellular responses and consequently partial protection against acute toxoplasmosis in C57BL/6 was confirmed.